Ventral-inlay buccal mucosal graft urethroplasty in a 44-year old female patient with recurrent urethral stricture. Issue 2 (6th February 2023) - Burkhardt, Orlando; Schmid, Hans-Peter; Engeler, Daniel; Zumstein, Valentin
Abstract: Female urethral stricture is a rare manifestation of bladder outlet obstruction in women. According to the current guidelines of the European Association of Urology, urethral dilatation should be offered as first line treatment. Intermittent self-dilatation (ISD) in case of recurrence is recommended. However, if patients wish definitive surgical treatment or are not able to perform ISD, urethroplasty can be considered. So far, there are little data available on urethroplasty in female patients. We present a case of a 44-year old female patient with a postoperative urethral stricture who underwent ventral-inlay buccal mucosal graft urethroplasty due to inability to perform ISD.